Perbaikan Proses Delivery Dokumen Maintenance C-Check Pesawat dengan Metode CCFE, FMEA, dan PICA (Studi Kasus di PT. GMF Aeroasia Tbk.) - Suryatman, Tina Hernawati; Putra, Muhammat Adi (Journal Industrial Manufacturing, 2021)
PT. GMF Aeroasia, Tbk is a company engaged in aircraft maintenance services. The aircraft maintenance lead time is regulated according to the agreement set forth in the agreement in the form of a work order, when the maintenance process takes place there is almost always a delay when working on the aircraft, both in terms of physical work or delivery of documents. These problems are several forms of waste, where waste is any activity that does not provide added value. Therefore, the purpose of this study is to identify the type of waste and determine the factors that cause waste in the delivery process of aircraft c-check maintenance documents. The method used in this study used a fishbone chart, cause failure mode effect, failure mode and effects analysis and problem identification and corrective action. Fishbone chart and cause failure mode effect are used to find waste that causes delay in document delivery, then analyzed using failure mode and effects analysis, three causes of the highest delay were found, namely stamps on incomplete documents (RPN 16), waiting for customer approval (RPN 16) and material certificates not available (RPN 12). Corrective Action was prepared as a recommendation to improve the delivery process for aircraft c-check maintenance documents. By knowing the types of waste and the factors causing waste in the delivery process of aircraft c-check maintenance documents at PT. GMF Aeroasia Tbk is expected to reduce waste and fulfill customer satisfaction. Keywords: Lead Time, Waste, Delay Delivery of Documents, Cause Failure Mode Effect Method, Corrective Action